IMPLEMENTASI EVALUASI PEMBELAJARAN ANAK USIA DINI DI KB AISYIYAH QURROTA AYUN BOJONEGORO - Nurul Novitasari Novitasari (UIN Kiai Ageng Muhammad Besari, 2023)
Evaluating learning is an activity that is said to be very important to do in order to know the success in a learning process which will be informed to children and parents of students. This evaluation can be used as a benchmark for the extent of student development and can be very helpful for educators to follow up if there are problems and delays in the learning process that students receive. Evaluation of learning in KB Aisyiyah Qurrota Ayun Bojonegoro was carried out based on research results from observations, interviews, and documentation analysis of learning at KB Aisyiyah Qurrota Ayun Bojonegoro. The implementation of the Learning Evaluation at the Bojonegoro KB Aisyiyah Qurrota Ayun Bojonegoro was carried out when learning was taking place through natural observations of children, with questions and answers or observations. The assessment tools used in the KB Aisyiyah Qurrota Ayun Bojonegoro are the results of the work, anecdotal notes, and the Rating Scale. This assessment instrument is used to assess the results of children's development as a basis for description at the end of the semester report. This assessment can also be used as an indicator of a child's ability to receive.